Rings of Saturn: Fellini Rosi1. Issue 3 (1st June 2022) - Gordon, Robert S. C.
This article offers a comparative reading of Gianfranco Rosi's Sacro GRA ('Holy GRA') (2013) and Federico Fellini's Roma (1972). It sets Sacro GRA within Rosi's career, his ambiguous identity as an 'Italian' filmmaker and the film's relation to the history of cinema in/on Rome and psycho-geographical road movies. It moves on to analyse Rosi's treatment of place and urban space, comparing key motifs and patterns in Sacro GRA with the short episode of Fellini's Roma, also set on the GRA, Rome's urban outer ring road. This dual reading is articulated around four axes of comparison in the construction and evocation of the ring-road space: street furniture, metacinematic frames and recordings, noises and silences, machines and monsters. Through these and other incidental constellations, the article argues that the two films display parallel, at times symmetrical, fascinations with the urban as simultaneously a space of utopia and dystopia, nature and the man-made, past and future.